2017
DOI: 10.7326/m17-0598
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes in Dose Reduction or Discontinuation of Long-Term Opioid Therapy

Abstract: Veterans Health Administration. (PROSPERO: CRD42015020347).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
306
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(314 citation statements)
references
References 95 publications
4
306
0
4
Order By: Relevance
“…Para ello realizaron una búsqueda bibliográfica de estudios originales publicados en inglés que tuvieran en cuenta la reducción de dosis o la interrupción del LTOT en dolor crónico en bases de datos biomédicas como MEDLINE, EMBASE, PsycINFO, CINAHL y Cochrane hasta abril del año 2017. Todos los autores evaluaron la calidad de la evidencia utilizando el sistema GRADE (Grading of Recommendations Assessment, Development and Evaluation) (17).…”
Section: Sr Directorunclassified
See 2 more Smart Citations
“…Para ello realizaron una búsqueda bibliográfica de estudios originales publicados en inglés que tuvieran en cuenta la reducción de dosis o la interrupción del LTOT en dolor crónico en bases de datos biomédicas como MEDLINE, EMBASE, PsycINFO, CINAHL y Cochrane hasta abril del año 2017. Todos los autores evaluaron la calidad de la evidencia utilizando el sistema GRADE (Grading of Recommendations Assessment, Development and Evaluation) (17).…”
Section: Sr Directorunclassified
“…Según esta revisión, una evidencia de "muy baja" calidad sugiere que varios tipos de intervenciones pueden ser eficaces para reducir o interrumpir el LTOT y que el dolor, la función y la calidad de vida pueden mejorar con la reducción de dosis de opioides (17).…”
Section: Sr Directorunclassified
See 1 more Smart Citation
“…According to recent systematic reviews, many studies examining interventions for dose reduction or discontinuation of long-term opioid use are of poor quality with uncontrolled designs. 2 Hadlandsmyth et al 6 and other studies have shown promising developments in fighting the opioid crisis. Nonetheless, there is more work to do.…”
mentioning
confidence: 99%
“…In the same year, over 33,000 people died of opioids and approximately 40% were attributed to opioid prescriptions, 1 contributing to what the Centers for Disease Control and Prevention (CDC) termed an Bepidemic.^Long-term opioid use is particularly problematic, associated with much higher rates of misuse and overdose than short-term use. 2 As we reconsider the appropriate role of opioids in medical care, experts have called for an effort to minimize the initiation of long-term use and to taper long-term patients off opioids, when warranted.…”
mentioning
confidence: 99%